MODEL PENERIMAAN TEKNOLOGI INTERNET PADA MAHASISWA DI KOTA SEMARANG - Mohammad Hasanudin (Jurnal Riset Akuntansi dan Keuangan, 2009)
Theoretical and ernpirical research on technologt acceptance, while aclmowledging the importance of individual beliefs about the compatibility of a technologt, has pro&tced equivocal results. This research revians studies using the TechnologtAcceptance Model (TAM| in order to create a modified model and instrument to study the acceptance of Internet technologt by students in semarang town. In this paper, we examined the relationships between the TAM constructs to explain thevmiance in the acceptance of different information technologies. Based upon the empirical research using the technologt assessrnent model, a modifi.ed TAM was developed for the acceptance of Internet-based technologies by students. and add or change one part of the TAM. The purpose of this study is (1) to apply the TAM to Internet technologt to be useful antecedents for predicting perceived usefulness, perceived ease of use and behavioral intent to use. Subject of the resemch is studentsin Semarang town, They asked tofill the qutionair abo;ut perception in internet.Keywords: Prerceived, ease of use, attitude, technology acceptance model, behavior, internet